(untitled) (MAUSAM, 1979)
The severe cyclone, which struck the Tamilnadu coast near Nagapattinam on 12 November 1977, was observed by the Cyclone Warning Radar at Madras from the 10th upto a few hours after landfall. The storm followed a westerly course with a slight southerly component. The most important feature was as eye shrinking gradually to an extremely small size suggesting intensification into a severe storm with a small core on the night of 11 November. The left sector of the eye wall was better developed. It may be mentioned that the radar sees the centre of the storm and the synoptic centre . However the touring officer’s report corroborates, that the severe damage was mainly to the south of Nagapattinam and confined to a narrow strip, thus agreeing with the radar positioning. The rest of the radar echoes were concentrated in right sector with a particularly prominent rainshield in the night rear sector (an unusual feature), giving heavy rainfall after the passage of the storm, This is confirmed from the rainfall distribution on 12th and 13th. The 2-day cumulative rainfall map of 12th and 13th shows three areas of maximum precipitation, one coinciding with the point, of landfall and the second showing the usual extension of the heavy rainfall belt northwards .The third maximum which was well Inland, resulted In the bursting of the Kudaganaru earthen dam. The meteorological data as well as a knowledge of the structural damage tend to suggest that the storm was a severe one with a small was a severe one with a small core of hurricane winds.